Learning in digital play: a dual case study of video gamers' independent play - Weimin Toh; Fei Victor Lim (The Asia-Pacific Society for Computers in Education (APSCE), 2022)
Abstract This paper explores the implications of youths' out-of-school gaming practices for teaching and learning in formal and informal learning contexts. We report on a study where we examined the video game play of two youths using a case study approach. User experience approaches, e.g. the think-aloud protocol and interviews, were grounded in the theoretical framework of social semiotics to analyse the gameplay videos and to discuss the implications for the youths' learning. The paper contends that youths are demonstrating critical thinking, empathy, and multimodal literacy through their gameplay. We offer suggestions for how adults can use video games for youths' learning.